PENANAMAN NILAI – NILAI KEDISIPLINAN MELALUI PEMBIASAAN SHOLAT DHUHUR BERJAMAAH DI SMP MA’ARIF KOTA BATU - Lailatul Maharani; Anwar Sa’dullah; Fita Mustafida (VICRATINA, 2019)
Planting is a process, action and how to implant. Habit is something that is intentionally done repeatedly so that something can become a habit. This study discusses Cultivation of Values of Discipline Through the Habit of Dhuhur Prayer in the Middle School Ma'arif Kota Batu. The study used a qualitative research approach and descriptive research types. This study when collecting data using the method of observation, interviews and documentation. Researchers go directly to the field for data collection and as a research instrument. The results of the study are as follows: the habituation of the dhuhur prayer in the congregation of students is accustomed to dhuhur prayers every Monday to Thursday, through the dhuhur prayer congregation values are instilled namely prayer discipline, time discipline, discipline in rules.